En quête d’héritage : force et faiblesse de la volonté individuelle à travers les testaments (Valachie, fin xviiie - début xixe siècle) - Andreea-Roxana Iancu (L'Atelier du CRH)
Our approach unfolds in two steps. First, we recount two legal conflicts about testaments that reveal the place of the individual in the social network. We then open the study to the more general question of individual identity in relation to the land ownership. Taking as a starting point the relationship between individual, land and community, we identify the stranger, such as defined at the time as a person outside the family, and highlight his role in the definition and practice of inheritance.